International clinical guideline for the management of classical galactosemia: diagnosis, treatment, and follow‐up. Issue 2 (17th November 2016) - Welling, Lindsey; Bernstein, Laurie E.; Berry, Gerard T.; Burlina, Alberto B.; Eyskens, François; Gautschi, Matthias; Grünewald, Stephanie; Gubbels, Cynthia S.; Knerr, Ina; Labrune, Philippe; van der Lee, Johanna H.; MacDonald, Anita; et al.
Abstract: Classical galactosemia (CG) is an inborn error of galactose metabolism. Evidence‐based guidelines for the treatment and follow‐up of CG are currently lacking, and treatment and follow‐up have been demonstrated to vary worldwide. To provide patients around the world the same state‐of‐the‐art in care, members of The Galactosemia Network (GalNet) developed an evidence‐based and internationally applicable guideline for the diagnosis, treatment, and follow‐up of CG. The guideline was developed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. A systematic review of the literature was performed, after key questions were formulated during an initial GalNet meeting. The first author and one of the working group experts conducted data‐extraction. All experts were involved in data‐extraction. Quality of the body of evidence was evaluated and recommendations were formulated. Whenever possible recommendations were evidence‐based, if not they were based on expert opinion. Consensus was reached by multiple conference calls, consensus rounds via e‐mail and a final consensus meeting. Recommendations addressing diagnosis, dietary treatment, biochemical monitoring, and follow‐up of clinical complications were formulated. For all recommendations but one, full consensus was reached. A 93 % consensus was reached on the recommendation addressing age at start of bone density screening. During the development of this guideline, gaps of knowledge were identified in most fields of interest, foremost in the fields of treatment and follow‐up.